Domestic violence in countries of the former Yugoslavia: Review of the most important results of the surveys - Ćopić Sanja M. (Temida, 2003)
This paper contains some of the most important results of the survey on domestic violence in Serbia and Macedonia, as well as of the survey on violence against women that was conducted in BH Federation that also contains data about partner violence against women. These surveys have confirmed results of some other researches that domestic violence is one of the most serious but at the same time most hidden forms of victimisation. It represents the manifestation of power and control over the victim, leading to a loss of trust and threatening the safety domain. Women and children are the most affected by this form of victimization, while in most of the cases men are perpetrators. Bearing that in mind, the aim of the paper is to, on the basis of the analysis of survey results, point out the prevalence structure and some characteristics of domestic violence in the pos-war societies of the former Yugoslavia, with a particular emphasis of the impact of economy crisis and war on this issue.